INOVASI DESAIN PEMBELAJARAN PENDIDIKAN ANAK USIA DINI BERBASIS TEORI KECERDASAN MAJEMUK UNTUK MENSTIMULASI KOMPETENSI 4C - mawaddah, khusnul; Muammar, M Arfan (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The aim of this research is to determine the relevance of multiple intelligences to the formulation of an independent curriculum (Learning Achievements and Pancasila Student Profile) which is then used as a basis for developing the 4C abilities of early childhood. This research is qualitative research with a library research approach, in the data collection process using documentation techniques. The research results showed that, (1) 4C capabilities have a vital role in preparing a generation that has soft skills and hard skills to face global challenges; (2) Multiple Intelligences and the independent curriculum have relevance in the form of a description of the structure of the independent curriculum which consists of intracurricular activities (application of learning outcomes) and co-curricular activities (application of literacy student profiles); (3) The relevance results are then developed in the form of a learning plan, by determining learning objectives as the basis for creating the module.